Determination of Phloridzin and Other Phenolic Compounds in Apple Tree Leaves, Bark, and Buds Using Liquid Chromatography with Multilayered Column Technology and Evaluation of the Total Antioxidant Activity - Adamcová, Anežka; Horna, Aleš; Šatínský, Dalibor (Pharmaceuticals, 2022)
Apples are known to be a rich source of phenolic compounds, however detailed studies about their content in the individual parts of apple trees are reported rarely. For this purpose, we tested various stationary phases for the determination of phenolic compounds in leaves, bark, and buds. Phloridzin, phloretin, chlorogenic acid, rutin, and quercitrin were analyzed with high performance liquid chromatography coupled with diode array detection. A YMC Triart C18-ExRS 150 × 4.6 mm, 5 μm particle size analytical column with multilayered particle technology was used. The separation was performed with a mobile phase that consisted of acetonitrile and 0.1% phosphoric acid, according to the gradient program, at a flow rate of 1 mL/min for 12.50 min. The concentration of phenolic compounds from 13 cultivars was in the range of 64.89-106.01 mg/g of dry weight (DW) in leaves, 70.81-113.18 mg/g DW in bark, and 100.68-139.61 mg/g DW in buds. Phloridzin was a major compound. The total antioxidant activity was measured using flow analysis and the correlation with the total amount of phenolic compounds was found. This finding can lead to the re-use of apple tree material to isolate substances that can be utilized in the food, pharmaceutical, or cosmetics industries.